Transformasi Ekonomi Hijau: Pemberdayaan Pemuda Desa Kedungsekar Melalui Bank Sampah - Sujono Sujono; Sri Roekminiati; Sapto Pramono; Dendy Patrija W (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study explores the transformative role of youth empowerment through green economy initiatives, specifically focusing on the management of a waste bank in Kedungsekar Village, Indonesia. Facing mounting environmental challenges such as waste accumulation and pollution, the local community sought sustainable solutions by integrating environmental, social, and economic dimensions. The involvement of youth, characterized by creativity, digital skills, and strong social networks, has been pivotal in driving this transformation. The waste bank functions as a social innovation that not only addresses waste management issues but also generates economic opportunities through circular economy practices. By actively participating in waste segregation, collection, and sale, youth have acquired operational and financial skills, enabling them to become entrepreneurs and community leaders. This initiative has shifted youth from passive recipients to active agents of change, fostering community awareness and environmental responsibility. Employing qualitative case study methods, including interviews, observations, and document analysis, this research highlights how integrated efforts rooted in environmental sustainability and community participation can catalyze socio-economic growth. The theoretical framework draws on the concepts of green economy, youth empowerment, and social innovation, illustrating how these pillars are interconnected in fostering sustainable development. Findings reveal that the green economy approach, facilitated by youth engagement, enhances local resilience, creates employment, and promotes environmental conservation. This case exemplifies the potential of grassroots initiatives in achieving sustainable transformation at the village level, serving as a model for other rural communities facing similar environmental and socio-economic issues. The study underscores the importance of empowering youth as key drivers in the transition towards sustainable and inclusive development.